Pengaruh Kepemimpinan Situasional, Motivasi Kerja, dan Kepuasan Kerja Terhadap Kinerja Karyawan(Studi Pada Kantor Sentral PT Perkebunan Nusantara IV Regional II Unit Kebun Marihat) - Gideon Maruli Simamora, Naek; Sihombing , Marlon; Mardhiyah, Ainun; Marakali Siregar, Onan (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The development of a company is highly dependent on the performance of the human resources in the company. Situational leadership possessed by the company's leaders and the motivation and job satisfaction possessed by employees are important factors that can improve the company's overall performance. However, there has been a decline in employee performance at PTPN IV Regional II Marihat Unit in recent times. This is due to the lack of attention and appreciation given by the leadership and the lack of motivation and job satisfaction from employees. The form of this research is quantitative with a sample size of 40 respondents who are also the population in this study. Primary data in this study were obtained by distributing questionnaires directly and secondary data were obtained through literature studies. The results of this study indicate that situational leadership (X1), work motivation (X2), job satisfaction (X3) have a significant effect both partially and simultaneously on employee performance at the Central Office of PT Perkebunan Nusantara IV Regional II Kebun Marihat Unit. The determination coefficient test shows that there is a close relationship between situational leadership (X1), work motivation (X2), job satisfaction (X3) and employee performance with an R value of 0.971. Through the adjusted R square value, it is also known that the variables of situational leadership (X1), work motivation (X2), job satisfaction (X3) contribute 93,7% to the employee performance variable, while the remaining 6,3% is influenced by other variables outside this research model.